ANALYSIS OF ELEMENTARY STUDENTS’ PUBLIC SPEAKING SKILLS - Uung Gondo Saputro; Imam Agus Basuki; Ade Eka Anggraini (Primary: Jurnal Pendidikan Guru Sekolah Dasar, 2023)
This paper describes students' public speaking skills and barriers, and its solution. The research used a qualitative descriptive approach and data collection techniques used interviews, observations, and documentation. It was conducted for students in Class VI at one of the private elementary schools in Malang. The results of students' public speaking skills in elementary school are still low. The test results show that 61.3% of students still did not complete KKM score (77). Internal factors come from a lack of self-confidence and lack of courage in expressing ideas when public speaking, difficulty in choosing appropriate and correct words in Indonesian, and difficulty to express opinions or ideas in speaking. External factors are the community's living environment (local language use) that influences students' skills to speak.